2018
DOI: 10.1159/000487539
|View full text |Cite
|
Sign up to set email alerts
|

FcγRIIIA Negatively Impacts Humoral Immune Responses but Not Overall Lung Inflammation in an Ovalbumin-Induced Allergic Asthma Mouse Model

Abstract: Background: Fcγ receptors (FcγR) play substantial immune regulatory roles both positively and negatively in pathophysiological processes including allergy and asthma. Compared with FcγRIIB which is classically defined as an inhibitory receptor, mouse FcγRIIIA and its functional human homologue FcγRIIA have been assumed to be activating receptors. However, evidence demonstrating inhibitory regulation by mouse FcγRIIIA has recently been emerging. Objective: To dissect the contributory roles of mouse FcγRIIIA (hu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…In an ex vivo arm of the study, the expression levels of FcγRIIIA, FcγRIIB, and IgE were measured in human asthma patients. It was found that FcγRIIB negatively correlated with serum IgE; however, this was not the case for FcγRIIIA [19]. Interestingly, unlike previously published work [20-22], the work of Zhou et al [19] did not support the positive immune regulatory roles of mouse FcγRIIIA.…”
Section: Asthmamentioning
confidence: 86%
See 1 more Smart Citation
“…In an ex vivo arm of the study, the expression levels of FcγRIIIA, FcγRIIB, and IgE were measured in human asthma patients. It was found that FcγRIIB negatively correlated with serum IgE; however, this was not the case for FcγRIIIA [19]. Interestingly, unlike previously published work [20-22], the work of Zhou et al [19] did not support the positive immune regulatory roles of mouse FcγRIIIA.…”
Section: Asthmamentioning
confidence: 86%
“…Zhou et al [19] investigated the role of mouse FcγRIIIA and FcγRIIB in an OVA-induced mouse asthma model. Allergic asthma was induced using OVA in wild-type, FcγRIIIA, and FcγRIIB KO mice, respectively.…”
Section: Asthmamentioning
confidence: 99%
“…p-Nitrophenyl phosphate solution (Southern Biotechnology Associates) was used for color development, and absorbance at 405 nm was measured by a spectrophotometer. OVA-specific IgG, IgG1, IgG2b, and IgE titers were measured as previously reported (23).…”
Section: Serological Analysesmentioning
confidence: 99%
“…Splenocytes (2.5 × 10 5 per well) were plated into a 96-well roundbottom plate in the presence or absence of OVA (1 mg/mL) followed by culture at 37°C in 5% CO 2 for 72 hours. The Cell Counting Kit-8 (CCK-8, Dojindo Molecular Technologies) was added to each well and the cells were incubated at 37°C in 5% CO 2 for another 4 hours before being harvested for assessing the proliferative capacity of splenocytes (23). The culture supernatants were harvested for cytokine measurement.…”
Section: Antigen Recall Assaymentioning
confidence: 99%
“…Asthma is a chronic airway inflammatory disease with the characterizations of reversible airflow obstruction, goblet cell and smooth muscle hyperplasia, increased mucus production, hyperactivity and ultrastructural remodeling of the airways [1,2]. The prevalence of asthma in the developed countries is approximately 10 % of the population [3]. Inhaled glucocorticoids and β 2agonists are common pharmacological treatments for asthma [4].…”
Section: Introductionmentioning
confidence: 99%